RECONSTRUCTION OF HISTORICAL CITIES OF UZBEKISTAN - Dilshod, Lukmanov (Miasto Przyszłości, 2024)
This article examines the idea of ​​preserving monuments and determines their significance in the development of science, culture, and public education. and the study and organization of the spatial environment of monuments.